Relations between sexually transmitted infection diagnosis and sexual compulsivity in a community-based sample of men who have sex with men. Issue 4 (20th December 2007) - Dodge, B; Reece, M; Herbenick, D; Fisher, C; Satinsky, S; Stupiansky, N
Abstract : Objective: To assess relations between sexual compulsivity and a history of sexually transmitted infection (STI) diagnosis and testing among a community-based sample of men who have sex with men (MSM) in a mid-size urban area of the midwestern United States. Methods: Sexual health data were collected from 504 MSM in the metropolitan area of Indianapolis, Indiana, using a community-based participatory research approach. Sexual compulsivity scores were assessed using the Sexual Compulsivity Scale (SCS). Results: The reliability and construct validity of the SCS were determined to be high in the total study sample. Men who scored high on the SCS reported higher levels of sexual risk behaviour with both male and female partners and were significantly more likely to have been diagnosed with STI (including chlamydia, gonorrhoea, both hepatitis A and B, and syphilis) than other men. Men who scored high on the SCS were not more likely than other men to have been tested for STI, despite higher levels of sexual risk. Conclusions: The SCS may be useful as a supplemental instrument in public health programmes and healthcare settings that encourage men to assess their sexual behaviours and make decisions to pursue STI or HIV screening. For those already diagnosed with an STI, the SCS may help providers to identify the cognitive and affective components of sexual behaviours that increase the likelihood that an STI will be transmitted to a sexual partner.